KESERAKAHAN CELENG Ketamakan Dalam Kesadaran Moral - Mahamboro, Dionius Bismoko (Jurnal Teologi (Journal of Theology), 2013)
In the Javanese culture, the wild Boar is a symbol of greed or avarice. In this article, boar as a symbol is seen as a language for expressing moral consciousness. Moral consciousness of the dangers of avarice has been started since the beginning of the Christian era and passed on to us through present time in the form of the Doctrine of the seven principal or deadly Sins. So here is presented the evolution of this consciousness perceiving greed as a moral problem, especially in the Biblical and Patristic tradition. Given that the use of wild Boar as a symbol of greed is associated with sociological background, the article shows also the reception of avarice as one of the seven deadly sins in the sociological science. These two different perspectives of how one speaks about avarice as a moral problem are useful to develop a more comprehensive understandings on avarice and a contextual language, expressing it as a moral issue that should never be overlooked in Indonesia.